Electrical properties and magnetoresistance effect of Nd doped La0.5Ba0.5MnO3 manganites for low field applications - Abdullah, Huda; Abdul Halim, Shaari; Lim, Kean Pah; Lee, O. J.; Elias, Saion; Ab. Aziz, Sidek; Zainuddin, Hishamuddin (Universiti Putra Malaysia Press, 2005)
Polycrystalline of (La1-xNdx)0.5Ba0.5MnO3 with x = 0, 1/6, 1/3, ½, 2/3, 5/6 and 1 has been prepared using solid state reaction. The effect of substituting neodymium at Lasite on magnetoresistance (MR) effect has been investigated. The doped samples are calcined at 900oC for 12 hours, pelletized and sintered at 1300oC for 24 hours. The magnetoresistance (MR) was measured at a magnetic field of H ≤ 1T at 90K, 100K, 150K, 200K, 250K, 270K and 300K. Overall, MR drops slowly when temperature rises. All doping concentration gives small variation range (~8.97% to ~63.49%). The highest MR value of 63.49 % was observed at 150K for sample of x = 1.0. The metal-insulator transition temperature, TP shifted towards lower temperatures as Nd doping increased, Tp followed by decreasing of the activation energy (Ea), which are 254, 244, 218, 198, 146, 130 and 114 K for the bulks with x = 0, 1/6, 1/3, ½, 2/3, 5/6 and 1, respectively. In the semi-conducting portion, activation energy (Ea) decreases as the doping concentration increases.